An Analysis of Sensory Integration Approach on Counting Skills Among Children With Special-Needs - Syaiful Huda; Nina Agustyaningrum (Universitas Malikussaleh, Aceh Utara, Indonesia, 2019)
This study aims at: (1) knowing whether there is an influence from the sensory integration approach using brain gym treatment and meronce (bead stringing) activities towards counting skills among children with special needs; (2) describing the effect of the sensory integration approach through brain gym treatment and meronce activities on counting skills among children with special needs. This study used the mixed methods with sequential explanatory design. The data analysis techniques were quantitative data analysis with SSR (single subject research) with A-B-A design and qualitative data analysis with data reduction, data display, as well as conclusions drawing and verification. The data were collected from the results of observations, interviews, tests, field notes, and documentations. The objects in this study were the students from the Philea Therapy Center, Batam. Based on the research findings, some conclusions can be drawn as follow: (1) there is a positive effect of the sensory integration approach through brain gym treatment and meronce activities on the counting skills among children with special needs in which the mean level in pre-test (A) was 50, treatment (B) was 83,33, and post-test (A) was 86.66, respectively; (2) sensory integration approach with brain gym treatment and meronce activities has a positive influence on the counting skills among children with special needs.